Virtual reality as an alternative to reproduction - Matti Häyry (Discover Artificial Intelligence)
Abstract Abiding by two intuitive ethical rules—“Do not contribute to the production of suffering” and “Do not make self-conscious species extinct without their consent”—at the same time presents a difficulty. Since all sentient beings suffer, we should, to obey the first rule, prevent all future reproduction. But if we do, our species will go, against the second rule, involuntarily extinct. Artificial intelligence could, in principle, be a way out of this dilemma. If we could, by mind uploading, move to a virtual reality with no suffering, the problem would be solved. This, however, has both practical and theoretical challenges.